2005
DOI: 10.1536/ihj.46.13
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Inhibitory Effects of Cilostazol and Ticlopidine on Subacute Stent Thrombosis and Platelet Function in Acute Myocardial Infarction Patients With Percutaneous Coronary Intervention

Abstract: SUMMARYWe compared the effects of ticlopidine and cilostazol on the prevention of subacute stent thrombosis (SAT) in acute myocardial infarction (AMI) patients with stenting. We also analyzed the cause of the difference by measuring platelet aggregation activity.Consecutive patients who underwent successful stenting for AMI between The incidence of SAT within four weeks after stenting was analyzed. Thirty-eight AMI patients were randomized and their platelet aggregation activity was measured using a laser-scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Cilostazol has been shown to inhibit the aggregation response to various agonists in blood from healthy individuals, CAD and PAD patients. 18,23,24 Similar effects have also been described with aspirin. 23,25 The effect of combination treatment with aspirin and cilostazol has been investigated in patients with IHD by Tanigawa et al Aggregation studies demonstrated that combination treatment significantly inhibited AAinduced aggregation.…”
Section: Discussionsupporting
confidence: 60%
“…Cilostazol has been shown to inhibit the aggregation response to various agonists in blood from healthy individuals, CAD and PAD patients. 18,23,24 Similar effects have also been described with aspirin. 23,25 The effect of combination treatment with aspirin and cilostazol has been investigated in patients with IHD by Tanigawa et al Aggregation studies demonstrated that combination treatment significantly inhibited AAinduced aggregation.…”
Section: Discussionsupporting
confidence: 60%
“…27) However, we did not perform an IVUS study. In addition, we do not know whether our observations for the ACE inhibitor group may have been influenced by a relatively weaker antiplatelet coagulation effect of cilostazol compared to ticlopidine 28) and a possible resultant difference in the effect of platelet-derived growth factor. Finally, we did not investigate the histopathological mechanisms of in-stent restenosis and its modification by the therapies.…”
Section: Effect Of Basal Antiplatelet Treatmentmentioning
confidence: 89%
“…However, there have been few studies of the impact of dipyridamole treatment on long-term outcome in patients with LV dysfunction. 19,20 Though our study is limited by the fact that it was retrospective, involving an observational cohort, propensity analysis was used to adjust for the different backgrounds. 21 Thus, our data demon- strated that dipyridamole therapy was effective in terms of long-term clinical outcomes in Japanese patients in whom complete revascularization was achieved.…”
Section: Discussionmentioning
confidence: 99%